2023
DOI: 10.1001/jamahealthforum.2023.0351
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Performance Measures and Service Volume at US Federally Qualified Health Centers During the COVID-19 Pandemic

Abstract: ImportanceStay-at-home orders, site closures, staffing shortages, and competing COVID-19 testing and treatment needs all potentially decreased primary care access and quality during the COVID-19 pandemic. These challenges may have especially affected federally qualified health centers (FQHCs), which serve patients with low income nationwide.ObjectiveTo examine changes in FQHCs’ quality-of-care measures and visit volumes in 2020 to 2021 vs prepandemic.Design, Setting, and ParticipantsThis cohort study used a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Hospitals/IDS initiation baseline rates and rate changes held year to year, suggesting hospital and IDS partners were better resourced in the face of the pandemic than FQHCs. This data supports the well-documented challenges faced by publicly supported health systems during the first year of the pandemic, including a substantial drop in patient population 28 , 29 and a decrease in the number of routine pediatric vaccine ordering and doses. 15 Additionally, while we observed higher rate changes among IDS/hospital partners, we were unable to detect significant differences in vaccination rate change between the two types of health systems.…”
Section: Discussionsupporting
confidence: 81%
“…Hospitals/IDS initiation baseline rates and rate changes held year to year, suggesting hospital and IDS partners were better resourced in the face of the pandemic than FQHCs. This data supports the well-documented challenges faced by publicly supported health systems during the first year of the pandemic, including a substantial drop in patient population 28 , 29 and a decrease in the number of routine pediatric vaccine ordering and doses. 15 Additionally, while we observed higher rate changes among IDS/hospital partners, we were unable to detect significant differences in vaccination rate change between the two types of health systems.…”
Section: Discussionsupporting
confidence: 81%
“…As of 2022, 90% of FQHC patients had incomes below 200% of the federal poverty level and 50% were covered by Medicaid (Health Resources and Services Administration, 2022a). Like other providers, FQHCs were substantially impacted by the COVID-19 pandemic in terms of service volume, measured quality, and shifts in care delivery (ie, telehealth use) (Cole et al, 2023; Kim et al, 2020). Evidence suggests that FQHCs were a crucial source of care throughout the pandemic and provided necessary access to COVID-19 vaccinations, testing, and treatment of patients from diverse racial and ethnic groups (Cole, Raifman et al, 2022; Kaiser Family Foundation, 2022).…”
mentioning
confidence: 99%
“…These 3 key PHE changes may interact in important ways with the changing needs of FQHC patients : Many FQHCs have indicated that their patients' needs differ from prepandemic, including increased needs for mental health and substance use disorder (SUD) services (Adepoju & Valdez, 2023). Although most FQHCs offer mental health and SUD services on-site, many expanded these services during the pandemic (Cole et al, 2023; Kaiser Family Foundation, 2022). Expanded service capacity was made possible, in part, through supplemental and enhanced federal funding during the pandemic.…”
mentioning
confidence: 99%